Microcontroller-based fetal heart motion emulator: article / Norzulaikha Zakaria - Zakaria, Norzulaikha (2010)
The previous fetal heart motion emulator system was operated and controlled by a computer. The system was inflexible to be transported from one place to another and required a high cost to build. After a few years, people move toward design that is portable and cost effective.